2019
DOI: 10.1177/1461444819888398
|View full text |Cite
|
Sign up to set email alerts
|

Digital participation? Internet use among adolescents with and without intellectual disabilities: A comparative study

Abstract: Internet use is an integrated part of everyday life, especially among young people. However, knowledge of this for young people with disabilities is scarce. This study investigates digital participation of adolescents with intellectual disabilities by comparing aspects of Internet use among adolescents with and without intellectual disabilities. Cross-sectional comparative design was used and a national survey from the Swedish Media Council was cognitively adapted for adolescents with intellectual disabilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 34 publications
(84 reference statements)
2
36
0
1
Order By: Relevance
“…Meanwhile, our findings were similar to the Internet use among adults with IDD in Spain and in Sweden (Ågren et al, 2019;Chiner et al, 2017 Notably, adults with IDDs perceived fewer benefits of using the Internet regarding increased knowledge, or work or study efficiency.…”
supporting
confidence: 82%
“…Meanwhile, our findings were similar to the Internet use among adults with IDD in Spain and in Sweden (Ågren et al, 2019;Chiner et al, 2017 Notably, adults with IDDs perceived fewer benefits of using the Internet regarding increased knowledge, or work or study efficiency.…”
supporting
confidence: 82%
“…Thus, we can elucubrate that older students with intellectual disability probably have enough experience with watching videos for learning, which would allow them to develop efficient regulation strategies, as in text reading. In fact, as previous studies have shown, individuals with intellectual disability report to watch videos for learning and for fun more frequently than other text‐based activities like reading news (Alfredsson Ågren et al, 2020; Delgado et al, 2019).…”
Section: Discussionmentioning
confidence: 87%
“…This is particularly astonishing considering that the smartphone, as a so-called smart product (Lee & Shin, 2017), contains many technical functions and possibilities to facilitate access to the Internet for this group of people (e.g., read aloud function, text reader, autocomplete functions). Ågren, Kjellberg, and Hemmingson (2019) revealed that Internet usage between young people with and without intellectual disabilities (aged between 13-20 years) differed in a significantly lower proportion in terms of "access to internet-enabled devices and performed ac-tivities…than the reference group." The authors noted, however, that some web applications are associated with a high degree of cognitive and linguistic skills that arise as barriers for people with intellectual disabilities.…”
Section: Research On Internet Usage Of People With Intellectual Disabilitiesmentioning
confidence: 99%